The images in the Floripa Guide: an analysis of the real city and the city represented (Terr@ Plural, 2020)
This paper aims to broaden analytical horizons for the approach of contemporary images as producers of the geographical imaginaries about places. For this, we analyzed images of Florianópolis published in a tourism brochure called Floripa Guide. The research was the theoretical framework for visual culture scholars such as Gillian Rose, Verónica Hollman, and Gisele Girardi. From the analysis of the context of the images formed both by the physical support in which they are presented, as well as by the linguistic and visual surroundings that compose them. The analysis of the images demonstrated how the visual records bear a certain version of reality, which generates geographic imaginations about the represented city. The Floripa Guide presents the city of Florianópolis as a place of harmonious relations between the preservation of nature and progress, emphasizing coastal natural aspects and the promotion of quality of life.
Keywords: Representation; Visual culture; Geographic imaginations